Inside Front Cover: Hybrid nano‐ and microgels doped with photoacoustic contrast agents for cancer theranostics (View 6/2021). Issue 6 (17th December 2021) - Xiao, Yu; Gateau, Jérôme; Silva, Amanda K A; Shi, Xiangyang; Gazeau, Florence; Mangeney, Claire; Luo, Yun
Abstract : Photoacoustic imaging (PAI) is an emerging noninvasive and low‐cost technology offering unprecedented opportunities to visualize cancer tissues. This technique combines optical excitation and ultrasound detection, providing large imaging depth, high resolution and excellent sensitivity. Besides, the use of contrast agents has boosted PA imaging specificity and has been applied in a wide range of clinical sets. Particularly, biocompatible and biodegradable hybrid nano‐ and microgels doped with PAI agents have been designed as innovative multimodal tools for cancer diagnosis and therapy, due to their high loading capacity, versatility for surface modification, rapid response to external stimuli and prolonged blood circulation time. All these are concluded by Florence Gazeau, Yun Luo and their co‐workers in article number 20200176 .